1975
DOI: 10.1007/bf01731728
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-associated RNA content of heterochromatin and euchromatin

Abstract: Chromatin from TLT hepatoma cells, mouse liver cells, and mouse brain cells was fractionated by differential centrifugation into a pellet, enriched with heterochromatin, and a supernatant, enriched with euchromatin. The pellet was found to contain more than twice as much of a particular species of chromatin-associated RNA per milligram chromatin DNA as did the supernatant. This chromatin-associated RNA was also found to be associated with the transcriptionally inactive chromatin of mature avian erythrocytes. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

1982
1982
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 43 publications
0
36
0
1
Order By: Relevance
“…While the reports on RNA with a putative chromatin organizing function date back to the 1960s and 1970s, [17][18][19] progress in the field has been hampered by the inability to identify the sequences of the involved RNAs, and to investigate the structural effects of RNA under conditions that preserve the native state of chromatin. Taking stock of nuclear RNAs by sequencing is now becoming in mechanism 4 has so far not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…While the reports on RNA with a putative chromatin organizing function date back to the 1960s and 1970s, [17][18][19] progress in the field has been hampered by the inability to identify the sequences of the involved RNAs, and to investigate the structural effects of RNA under conditions that preserve the native state of chromatin. Taking stock of nuclear RNAs by sequencing is now becoming in mechanism 4 has so far not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, reports that RNA is an integral component of chromatin have been published already in the 1970s [22].…”
Section: Introductionmentioning
confidence: 99%
“…As RNA is a critical component for chromatin organization and RNA is twice as prevalent as DNA in purified chromatin fractions, there is no doubt that RNA-chromatin networks should the primary determinants of epigenetic control (Maison et al, 2002;Paul and Duerksen, 1975). In the following sections, we will focus on the lncRNA Xist to illustrate how these intriguing lncRNAs are designed to orchestrate crosstalk between the RNA and chromatin worlds.…”
Section: The Emerging Theme Of An Rna-chromatin Networkmentioning
confidence: 99%
“…Around 20 years later, Paul and Duerksen surprisingly found that biochemically purified chromatin fractions contain more than twice as much RNA as DNA (Paul and Duerksen, 1975), raising the suspicion that RNA may be the primary organizer of chromatin structure and epigenetic regulation. This underlying "dark matter" was extensively appreciated by transcriptome sequencing, which revealed that while ~1% of the mammalian genome carries protein-coding potential, more than 75% of the genome is transcribed to produce a huge number of non-coding transcripts, including rRNAs, tRNAs, snRNAs, miRNAs, siRNAs, piRNAs, and especially lncRNAs (Djebali et al, 2012;Lander et al, 2001;Venter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%